Towards a stringy extension of self-dual super Yang-Mills; Physics Letters B; Vol. 460, № 3-4 - Galajinsky A. V. Anton Vladimirovich (1999, 1999)
Motivated by the search for a space-time supersymmetric extension of the N = 2 string, we construct a particle model which, upon quantization, describes (abelian) self-dual super Yang-Mills in 2+2 dimensions. The local symmetries of the theory are shown to involve both world-line supersymmetry and kappa symmetry.